Conclusion - war and community: what have we learned about their relationship? - Elcheroth, Guy; Spini, Dario; Čorkalo Biruški, Dinka (2014)
The last chapter summarises the empirical findings and theoretical accounts provided in the book by making a statement that the former Yugoslavia experiences have clearly shown an illuminating pattern of societal destabilisation, destruction and restoration ; whereas the old political structures were decomposed fairly rapidity and new ones were established with the same speed, the communal and community life of people went through a long period of disbelief and despair, caused by massive violence, ethnic cleansing and unimaginable atrocities committed very often by a neighbour or a schoolfellow. The long-lasting consequences of war are most notable in the slow and painful processes of social recovery of once highly integrated communities. Many empirical findings in the book show that former everyday practices of interethnic contacts, friendships and mixed marriages have been profoundly changed and replaced by external identity labels as ultimate elements of social exchange. The former Yugoslav case therefore also invites to a more careful consideration of the relationship among historical contexts, social practices and collective identity as well as perhaps to re-imagine scientific approaches through which the understanding of these phenomena may be further enhanced. The proposed conclusion first comes back to the original question of how ethnic categories became social facts in the former Yugoslavia ; then, it attempts to summarise what can be learned about the collective dimensions of trauma more generally. Finally, the authors abstract more general ideas regarding promising interdisciplinary approaches that could be used in the social sciences to develop knowledge of (other) communities affected by war.
Projekt MZOS